(untitled) (Eurasian Research Bulletin, 2023)
This article presents the findings of the social survey conducted in the frame of the dissertation related to women’s empowerment in rural areas of Uzbekistan. The sociological analysis of the role and status of rural women has made it possible to analyze in depth the gender specificity of indicators of women’s socio-economic well-being and to develop recommendations for reducing the gender gap in the social, economic and sociopolitical spheres. The study was conducted on proportionally selected samples of representatives in four regions of the Republic of Uzbekistan: Tashkent, Fergana, Surkhandarya, and Khorezm. It is concluded that despite the regional characteristics of each region, agriculture is not only the main source of income, but also opens up new opportunities for the development of entrepreneurship, business management and information technology, thereby demonstrating the transformation of the status of rural women by improving their professional skills and involving them in new areas of work in entrepreneurship.